Are people with schizophrenia adherent to diabetes medication? A comparative meta-analysis. (April 2017) - Gorczynski, Paul; Firth, Joseph; Stubbs, Brendon; Rosenbaum, Simon; Vancampfort, Davy
Abstract: Individuals living with schizophrenia are 2–3 times more likely to experience type 2 diabetes mellitus. Diabetes medication adherence is essential to reduce morbidity and mortality in this population. We conducted a meta-analysis of diabetes medication adherence among people with schizophrenia, and compared this to those without schizophrenia. A systematic search strategy was used to identify all articles reporting adherence to diabetes medications among patients with schizophrenia. In total, 10 unique studies reporting data from 33, 910 people with schizophrenia were included. Random effects meta-analysis showed people with schizophrenia adhered to medication on 77.3% of days prescribed (n=32080, 95%CI=73.6–81%, I 2 =99.2%, ), and adhered on 4.6% more days per year than those without schizophrenia (p<0.01, 95%CI=2.4–6.7%, I 2 =92.5%, schizophrenia n=19367, controls=170, 853). Furthermore, 56% of individuals with schizophrenia (n=33680) were considered "adherent" (i.e. >80% adherence over 12–24 month) to diabetes medication, which was significantly more than those without schizophrenia (OR=1.34, 95%CI: 1.18–1.52, p<0.01). Factors which were positively associated with diabetes medication adherence were age, number of outpatient visits, along with multiple medication administration variables. Future prospective research should examine diabetes monitoring, medication prescription, and subsequent adherence in fully representative samples. Novel interventions for maximizing compliance to diabetes medication in this vulnerable population should also be explored. Highlights: People with schizophrenia are highly susceptible to type 2 diabetes mellitus. Diabetes medication adherence is essential to reduce morbidity and mortality. People with schizophrenia are less likely to receive diabetes education and care. Diabetes medication adherence is higher in people with schizophrenia. Diabetes medication adherence in people with schizophrenia is influenced by age.